Oxide‐Based Solid‐State Batteries: A Perspective on Composite Cathode Architecture. Issue 1 (20th November 2022) - Ren, Yaoyu; Danner, Timo; Moy, Alexandra; Finsterbusch, Martin; Hamann, Tanner; Dippell, Jan; Fuchs, Till; Müller, Marius; Hoft, Ricky; Weber, André; Curtiss, Larry A.; Zapol, Peter; et al.
Abstract: The garnet‐type phase Li7 La3 Zr2 O12 (LLZO) attracts significant attention as an oxide solid electrolyte to enable safe and robust solid‐state batteries (SSBs) with potentially high energy density. However, while significant progress has been made in demonstrating compatibility with Li metal, integrating LLZO into composite cathodes remains a challenge. The current perspective focuses on the critical issues that need to be addressed to achieve the ultimate goal of an all‐solid‐state LLZO‐based battery that delivers safety, durability, and pack‐level performance characteristics that are unobtainable with state‐of‐the‐art Li‐ion batteries. This perspective complements existing reviews of solid/solid interfaces with more emphasis on understanding numerous homo‐ and heteroionic interfaces in a pure oxide‐based SSB and the various phenomena that accompany the evolution of the chemical, electrochemical, structural, morphological, and mechanical properties of those interfaces during processing and operation. Finally, the insights gained from a comprehensive literature survey of LLZO–cathode interfaces are used to guide efforts for the development of LLZO‐based SSBs. Abstract : The perspective addresses the critical issues in the development of composite cathodes in solid‐state batteries based on a garnet LLZO electrolyte. The focus is on understanding various homo‐ and heteroionic interfaces and their chemical, electrochemical, structural, morphological, and mechanical properties during processing and operation. The knowledge gained from an extensive literature review is used to guide the optimization of oxide batteries.